Pathogenicity and genetic profile of oral Porphyromonas species from canine periodontitis - do Nascimento Silva, Amanda; de Avila, Erica Dorigatti [UNESP]; Nakano, Viviane; Avila-Campos, Mario J. (My University, 2017)
Objective In this study, the presence of the prtC and fimA genes involved in the pathogenicity of oral Porphyromonas spp. isolated from dogs with periodontitis and healthy, as well as their genetic diversity was investigated. Design Thirty-two Beagle dogs, 24 with periodontitis and 8 healthy were evaluated. Subgingival samples from only one gingival site of both groups were collected. Bacteria grown in anaerobiosis were identified by RAPID ID 32A kits. From each strain the respective DNA was obtained and used to genotyping by conventional PCR and AP-PCR. Results Dogs with periodontitis harbored 28 P. gulae, 2 P. creviocaricanis, 1 P. cangingivalis and 7 P. macacae; and from healthy dogs, 11 P. gulae and 5 P. circumdentaria. In P. gulae isolated from periodontal dogs the gene prtC was observed in 19 (67.85%) and in 7 (63.63%) from healthy dogs. P. gulae strains from periodontal dogs harbored either the gene fimA I or fimA II; while strains from healthy dogs harbored the gene fimA I, fimA II, fimA III or fimA IV, as well as 1 P. circumdentaria the gene fimA II. By AP-PCR strains were grouped in different clusters suggesting heterogeneity of these microorganisms. Conclusions The results presented herein inform that Porphyromonas spp. isolated from dogs with and without periodontitis harbored the prtC and fimA genes and it could be a role in the establishment of the infectious process.
Keywords: fimA gene; Genetic diversity; Periodontal disease; Porphyromonas spp.; prtC gene